Forehand overhead drop shot analysis for men's under-15 badminton athletes - Erawati, R.; Suratman, S. (Proceedings of the 6th International Seminar on Public Health and Education, ISPHE 2022, 29 June 2022, Semarang, Central Java, Indonesia, 2023)
Abstract. As a result of observation of men's under-15 athletes, many athletes still failed when they hit the forehand overhead drop shot. The formulation of the problem in this study is how to hit the badminton forehand overhead drop shot. This study aims to analyze the forehand overhead drop shot in badminton athletes.The research was conducted on the male under-15 athlete of The Satria Badminton Club, totaling 12 samples. The sampling technique used is random sampling. The data was obtained by analyzing the forehand overhead drop shot for 20 strokes with one recording using kinovea software on the racket grip, standing posture, footwork movement, arm swing, impact, and flight direction of the shuttlecock and continued by making the percentage of forehand overhead drop shot capabilities. The results showed that the men under-15 athletes of The Satria Badminton Club, Tegal regency, totaled 12. The forehand overhead drop shot assessment results are in a reasonably good category. The mistakes made by the athlete when making a forehand overhead drop shot were that the shuttlecock fell far from the net, the flight direction of the shuttlecock was too high, and the shuttlecock was not directed to the target. This study suggests that coaches need a training program to improve badminton athletes' forehand overhead drop shots in The Satria Badminton Club, Tegal regency.